2008
DOI: 10.1016/j.drugalcdep.2007.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Severity of childhood trauma is predictive of cocaine relapse outcomes in women but not men

Abstract: We prospectively examined the gender-specific effects of childhood trauma on cocaine relapse outcomes in an inpatient sample of treatment engaged cocaine dependent adults. Cocaine dependent men (n = 70) and women (n = 54) participating in inpatient treatment for cocaine dependence were assessed on severity of childhood trauma and followed for 90 days after discharge from treatment. Greater severity of childhood emotional abuse was associated with an increased risk of relapse in women. Severity of emotional abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
116
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(128 citation statements)
references
References 54 publications
(73 reference statements)
10
116
0
1
Order By: Relevance
“…Some studies show that exposure to trauma increases the risk of SUD (Kilpatrick et al, 2003;Sartor et al, 2007). Also, SUD patients with more severe histories of trauma seem more prone to substance use relapse (Westermeyer et al, 2001;Hyman et al, 2008) and show worse treatment outcomes compared to patients with less severe trauma (Brown and Wolfe, 1994;Hien et al, 2000). However, a longitudinal study by Chilcoat and Breslau (1998) showed that exposure to trauma in the absence of PTSD did not increase the risk of SUD.…”
Section: Introductionmentioning
confidence: 92%
“…Some studies show that exposure to trauma increases the risk of SUD (Kilpatrick et al, 2003;Sartor et al, 2007). Also, SUD patients with more severe histories of trauma seem more prone to substance use relapse (Westermeyer et al, 2001;Hyman et al, 2008) and show worse treatment outcomes compared to patients with less severe trauma (Brown and Wolfe, 1994;Hien et al, 2000). However, a longitudinal study by Chilcoat and Breslau (1998) showed that exposure to trauma in the absence of PTSD did not increase the risk of SUD.…”
Section: Introductionmentioning
confidence: 92%
“…For instance, post-traumatic stress disorder is associated with poorer adherence to MMT (Hien, Nunes, Levin, & Fraser, 2000), however, this has not been universally observed (Himelhoch et al, 2012). Furthermore, among cocaine dependent inpatients, severity of childhood trauma has been found to predict cocaine relapse among women but not among men (Hyman et al, 2008). MMT programs vary widely in the extent to which they provide treatments to address trauma exposure.…”
Section: Introductionmentioning
confidence: 97%
“…14 For example, in a cocaine treatment-seeking sample, greater severity of childhood emotional abuse increased the likelihood of cocaine relapse for women, but not for men. 33 In another US study, 34 childhood maltreatment among women, but not men, was associated with alcohol abuse or dependence in early adulthood, which was linked to excessive drinking in later adulthood. In a Midwestern US study, an increased likelihood of drug use problems was noted among women and not men.…”
mentioning
confidence: 99%